QIRĀ'ĀT SAB'AH IN THE TAFSIR NUSANTARA: IMPLICATIONS OF FARSY AL-ḤURŪF QS AL-A'RĀF IN THE TAFSIR MARĀḤ LABĪD - Dinda khoirunnnisa; Hana natasya (Al-Dhikra: Jurnal Studi Quran dan Hadis, 2025)
The study of Qira'at in Nusantara interpretation shows a unique methodological dynamic, especially in the use of qira'at sab'ah to enrich the meaning of verses. This article examines the implications of farsy al-Huruf in QS. al-A'raf as interpreted in Tafsir Marah Labid by Nawawi al-Bantani. This research uses qualitative literature-based study with comparative descriptive analysis of variations of qira'at sab'ah also using the discipline of Taujih al-Qira'at Science. The results show that Nawawi does not only refer to qira'at as philological data, but uses it as a hermeneutical instrument to expand the spectrum of meaning, syntactic structure, and strengthen theological and legal aspects in verses. This finding confirms that the Nusantara interpretation tradition has a close relationship with the authority of classical qira'at science, while also showing the methodological depth of Nusantara scholars' interpretation.